Visi dan perencanaan pemerintah daerah dalam perubahan global: Kajian pendekatan manajemen strategis - Hermada Dekiawan (Universitas Islam Indonesia, 1997)
In the globalization era, every government will have to be efficient and transparent. It is also applied to regional governments because they will deal with complex circumtances. For example, they will deal with foreign investors that will invest in the regional government's authority.